Serum calcium and phosphate levels and carotid atherosclerotic plaque characteristics: a retrospective study by high-resolution MR vessel wall imaging - Song, Xiaowei; Zhao, Hongliang; Pengmao, Zhuoma; Hou, Duoduo; Zhao, Xihai; Zheng, Zhuozhao; Wu, Jian (Frontiers in Neurology, 2025)
Background and aimsSerum calcium (Ca), phosphate (P), and calcium-phosphate product (CPP) are associated with cardiovascular disease and atherosclerosis in patients with chronic kidney disease. However, it remains unclear whether this relationship persists in individuals with carotid artery atherosclerosis of acute ischemic stroke. We investigated the association between serum Ca, P, as well as CPP, and carotid artery atherosclerotic plaque in acute ischemic stroke patients.Methods and resultsA total of 251 ischemic stroke participants with carotid artery atherosclerosis (mean age: 68 years; male: 80.1%) were retrospectively enrolled at a comprehensive stroke center. Serum Ca and P levels were obtained from blood tests after admission. Carotid artery plaque burden and vulnerability were evaluated using high-resolution magnetic resonance vessel wall imaging. Subsequently, the associations between serum Ca, P, as well as CPP, and the characteristics of atherosclerotic plaques were analyzed using multivariate linear and logistic regression analyses. Finally, the consistency of these associations was also explored across different subgroups. As a result, serum P and CPP levels were associated with carotid artery plaque burden, presented as maximum wall thickness (max WT), wall area, and lipid-rich necrotic core (LRNC), in univariate analysis, with β = −0.205, 95% CI (−0.348, −0.061), β = −0.258, 95% CI (−0.405, −0.113), OR = 0.182, 95% CI (0.034, 0.975) for P, and β = −0.203, 95% CI (−0.346, −0.059), β = −0.221, 95% CI (−0.366, −0.074), OR = 0.466, 95% CI (0.237, 0.915) for CPP, respectively. In multivariate regression analysis, the serum P level was independently associated with wall area, β = −0.211, 95% CI (−0.367, −0.052).ConclusionLower serum phosphorus levels are associated with an increased carotid artery plaque wall area.